Place of residence affects food preferences and satisfaction with diet among the elderly - Hartman-Petrycka, Magdalena; Lebiedowska, Agata; Blonska-Fajfrowska, Barbara (Social Welfare: Interdisciplinary Approach, 2015)
The study was conducted to determine specific differences in food preferences and satisfaction with diet between elderly people leading independent lives and those living in Social Welfare Homes. The studied group included 100 people. The participants were shown photographs of 22 types of dishes. They fulfilled the questionnaire about frequency and pleasure delivered from eating those dishes. Studies have shown that food preferences and satisfaction with diet among people over the age of 60 are highly dependent on their place of residence. Supervision and frequent inspections are needed to regulate nutrition in Social Welfare Homes in Poland.
Keywords: Social Welfare Homes; the elderly; food preferences; frequency of eating